Keanekaragaman Arthropoda pada Tanaman Bayam Merah (Amaranthus tricolor L.) yang Diberi Perlakuan Bokashi Jerami Padi - Difa Nanda Gemilang; Tuti Heiriyani; Nukhak Nufita Sari (Agroekotek View, 2022)
Arthropods or commonly known as segmented animals are closely related to the cultivation of plants such as vegetables. This is because arthropods can act as pests or natural enemies for plants. The existence of pests and natural enemies can be affected by various conditions, one of which is soil fertility. The use of rice straw bokashi in red spinach cultivation is expected to provide information on whether rice straw bokashi has an effect on the diversity level of arthropods in red spinach cultivation. This study used the RAK method (Randomized Block Design) 1 factor, consisting of 5 treatments with 4 groups, with a total of 20 experimental units in the form of J0: negative control, J1: positivecontrol (NPK Mutiara), J2: Bokashi 4 t.ha-1, J3: Bokashi 5 t.ha-1, J4: Bokashi 6 t.ha-1. From the observations obtained 12 arthropod orders, namely aranae, diptera,  lepidoptera, blattodea, hemiptera, coleoptera, isoptera, orthoptera,  hymenoptera, polydesmides,  odonata and spirostrepsids. The results showed that the administration of bokashi in various doses had no effect on the diversity, dominance, evenness and richness of arthropod species in red spinach. The diversity index is in the medium criteria, the dominance index is at the low criterion, the evenness index is at the high criterion, and the species richness index is at the low criterion.